The Plurivocal Character of Hermeneutics – Moving beyond the Quest for Objectivity - Liviu URSACHE (Annals of Philosophy, Social and Human Disciplines, 2014)
As a science, hermeneutics started out in the area of theology. Dealing with revealed texts, the interpreters would be interested in searching out for the authorial intent. Therefore, one could say that, at its beginnings, the interpretation was concerned with discovering the meaning that was already there, namely the meaning intended by the author. However, the history of Christian thoughts reveals that the schools of interpretations did not agree on the methods of hermeneutics. Things are not different now, except for the fact that it is much harder for the interpreter to reach the authorial intent due to the time gap. Though objectivity in interpretation is desirable, as it keeps the interpreters away from far off interpretations, it is impossible to achieve. In this article I underline the plurivocal character of hermeneutics as a result of interactions among the participants in the act of interpretation: the author, the text and the reader. While the first two keep the interpreter within some objective perimeters, the reader would never be a passive recipient of a text. The goal of hermeneutics is transformational rather than informational. Thus, the interpreter moves from the quest for objectivity to ontology